BRACU new campus development project construction schedule (1.06.22-30.06.22) - BUCG-ABC Joint Venture (BUCG-ABC JV) (Brac University, 2023)
This record consists of general correspondence regarding the submission of construction schedule from 1 June, 2022 to 30 June, 2022 of BRACU new campus project.